Feedback control systems - Phillips, Charles L (Prentice-Hall, 1996)
The material of this book is organized into three principal areas: analog control systems, digital control systems, and nonlinear analog control systems. Chapter 1 in this book presents a brief introduction and an outline of the text. Chapter 2 develops the transfer function model of linear analog systems, and chapter 32 develops the stae-variable model. Chapter 4 covers typical responses of linear analog systems, including the concept of frequancy responseImportant control-system characteristics are developed in chapter 5. Some of the applications of closed-loop systems are evident from these characteristics. The very important concept of system stability is developed in chapter 6 along with the Routh-Hurwitz stability criterion. Chapter 7 presents analysis and design by root locus procedures, which are basically time-response procedures. The equally important frequency-response analysis and design procedures are presented in chapter 8 and 9. Chapter 10 is devoted to modern control-system design. Chapter 11 through 13 applies to digital control systems. Nonlinear system analysis is presenbted in chapter 14. These methods include the describing-function analysis, linearization, and the state-plane analysis. Four appendices are included. The first appendix reviews matrices, the second appendix develops an analytical design procedure that applies to both root-locus design and Bode design. The third appendix reviews the Laplace transform, and the fourth apeendix is a table of Laplace transforms and z-transforms